Kandungan Flavonoid dan Serat Sesbania grandiflora pada Berbagai Umur Bunga dan Polong - Setiawan, Eko (Jurnal Hortikultura Indonesia (JHI), 2018)
ABSTRACTThe vegetable production in Madura islands is very limited due to dry soil conditions. The turi tree (Sesbania grandiflora) planted in Madura as barrier rice fields has the potential to be optimized as a source of vegetable. The objective of the study was to determine flavonoid and dietary fiber contents in flowers and fruits/pods of red and white turi that are picked at different ages. The research was conducted in December 2016 to March 2017 at Bangkalan. The study was arranged is Completely Randomized Design method with two factors and three replications. First factor was namely flower (red and white turi), and second factor is harvest time (turi flowers are harvested at 1, 2, 3, 4, 5, and 6 days; while the fruits/pods are harvested at 1, 2, 3, 4, 5, and 6 weeks after anthesis). The results showed that flavonoid contents in white turi flower ranged from 12.58-211.35 mg.100 g-1, whereas flavonoid contents in red flower ranged from 17.32- 30.05 mg.100 g-1. The highest flavonoid content is produced at 4-day-old flowers for white turi, and 4-5 day-old flowers for red flowers. The dietary fiber content in turi flower was higher in red than white flower ranged from 2.11-2.85% and 1.82-2.55%, respectively. The amount of dietary fiber in the fruits/pods was low, range from 0.013-0.686% and 0.009-0.722% in white and red turi, respectively. The flowers of turi should be consumed at 4-5 day-old flowers, while fruits/pods at 1-3 weeks after anthesis.Keywords: anthesis, functional vegetable, harvest time, Madura islandABSTRAKProduksi tanaman sayuran di Pulau Madura sangat terbatas karena kondisi tanah yang kering. Pohon turi (Sesbania grandiflora) yang ditanam sebagai pembatas tegalan dan sawah di Madura berpotensi untuk dioptimalkan sebagai sumber bahan sayuran. Penelitian bertujuan mengetahui kandungan serat dan flavonoid pada bunga dan buah/polong turi warna merah dan putih yang dipetik pada umur yang berbeda. Penelitian dilaksanakan di Bangkalan pada bulan Desember 2016 sampai Maret 2017. Penelitian menggunakan Rancangan Acak Lengkap dengan dua faktor dan diulang 3 kali. Faktor pertama adalah jenis bunga (turi bunga merah dan bunga putih), sedangkan faktor kedua adalah umur panen (bunga turi dipanen pada umur 1, 2, 3, 4, 5, dan 6 hari; sedangkan buah (polong) dipanen pada umur 1, 2, 3, 4, 5, dan 6 minggu setelah bunga mekar). Hasil penelitian menunjukkan kandungan flavonoid pada bunga turi putih berkisar antara 12.58-21.35 mg.100 g-1, sedangkan pada turi bunga merah kandungan flavonoid berkisar 17.32-30.05 mg.100 g-1. Kandungan flavonoid tertinggi dihasilkan pada bunga umur 4 hari untuk turi putih, dan bunga umur 4-5 hari untuk turi merah. Kandungan serat turi merah lebih tinggi dibandingkan dengan turi putih masing-masing dengan kisaran antara 2.11-2.85% dan 1.82-2.55%. Kandungan serat pada buah/polong turi sangat rendah berkisar antara 0.013-0.686% pada turi putih dan sebesar 0.009-0.722% pada turi merah. Bunga turi sebaiknya dikonsumsi pada umur 4-5 hari, sedangkan buah/polong pada umur 1-3 minggu setelah anthesis.Kata kunci: anthesis, Pulau Madura, sayuran fungsional, umur panen